What is the first step in solving the equation 3y + x = 6 for x?

A. Subtract 3y from both sides of the equation.
B. Subtract x from both sides of the equation.
C. Divide each side of the equation by 6.
D. Divide each side of the equation by 3.

Respuesta :

the answer is that you subbtract 3y from both sides sence you are solving for x
I think the correct answer among the choices listed above is option A. The first step in solving the equation 3y + x = 6 for x is to Subtract 3y from both sides of the equation. Solving for x is as follows:

3y + x = 6
3y + x - 3y = 6 - 3y
x = 6 - 3y
ACCESS MORE